Anti-Inflammatory, Gastrointestinal and Hepatoprotective Effects of Ocimum sanctum Linn: An Ancient Remedy with New Application - A′lam Kamyab, Amir; Eshraghian, Ahad (Inflammation & Allergy-Drug Targets (Discontinued), 2013)
Herbal medicine has a long background equal to history of humankind. Several plants have been used as remedies in ancient Persian, Egyptian, Chinese and Indian civilizations. The plant Ocimum sanctum Linn. (Tulsi) is one of these medicinal plants with a wide variety of applications in traditional medicine. In modern era, it has been shown to be effective against diabetes mellitus, hypertension, cancers, bronchitis, and found to have anti-microbial properties. Several experimental studies have confirmed its anti-inflammatory properties and its role in modulation of both cellular and humeral immunity. Recently its efficacy against inflammatory response, hepatic injury and gastric ulcer has been elucidated in animal studies. In liver, essential oils and extracts of Ocimum sanctum could prevent oxidative stress by increasing glutathione peroxidae and catalase and were also effective in prevention of hepatic steatosis. In gastric epithelial tissue different derivatives of Ocimum sanctum had anti-ulcer and anti-secretory characteristics and could heal gastric ulceration. These beneficial properties of this medicinal plant can mainly originate from its major biochemically active constituents like eugenol, carvacrol, ursolic acid, β-caryophyllene and rosmarinic acid. Here in, we reviewed current literature about anti-inflammatory, gastric and hepatoprotective properties of Ocimum sanctum.
Keywords: eugenol